Feasibility of Structured Assignment Sheet to Train The Ability to Draft a Frame of Mind in Solving Chemical Problems in Reaction Rate Materials - N. R. Janah; S. Suyono (Universitas Negeri Yogyakarta, 2022)
The study aimed to produce a feasible structured assignment sheet as a learning device. The structured assignment sheet was feasible to be used to train the ability to draft a frame of mind in solving chemical problems in reaction rate material. This developed learning device is named SAS-ADFM. The feasibility of SAS-ADFM included criteria of validity, practicality, and effectiveness. SAS-ADFM was developed using the Research and Development (R and D) method. SAS-ADFM was tested on 15 students of class XI who had obtained reaction rate material at SMAN 3 Surabaya. The instruments were the sheets of validation, student response questionnaire, and frame of mind drafting ability test. The validity of SAS-ADFM based on the assessment of three validators met the criteria of validity with a value of Mo ≥ 4 and R ≥ 75%. Meanwhile, the practicality of SAS-ADFM based on the analysis of the assessment of the student response questionnaire produced a very practical category with a percentage of 99%. Finally, the effectiveness of SAS-ADFM based on the analysis of the assessment of the ability to draft a frame of mind produced an N-gain score of 0.5 with a medium category. Hence, the developed SAS-ADFM was feasible to be used as a learning device.